Protein Adsorption Behavior on the Surface of the Microfiltration Membrane Based on a Quartz Crystal Microbalance (QCM) - Zhou Wang; Yadong Kong; Qian Zhang; Zhan Wang; Natsagdorj Khaliunaa; Rooha Khurram; Yuenan Zhou; Tungalagtamir Bold; Khan Bushra (Journal of Chemical Engineering Research Updates, 2018)
How to fast and efficiently determinate the fouling behavior of the microfiltration membrane has great significance for the industrial membrane application. In this paper, the MF membrane was put on the surface of a gold-coated quartz crystal of QCM to study the adsorption behavior of protein at different conditions. The adsorbed mass increased with the increasing of concentration, ionic strength and temperature while decreased with the increasing of pH. Then the BSA adsorption results were compared with the corresponding membrane flux in dead-end cell at the identical conditions. Furthermore, the BSA adsorption process can be described by Langmuir and Freundlich isotherms very well. These results suggested that directly putting the membrane on the surface of a gold-coated quartz crystal of QCM can be used as a rapid and efficient approach to study protein fouling on the membrane surface. This approach using QCM and a small piece of the membrane could yield quantitative information for adsorption kinetics investigation and reduce the workload in large-scale industrial project.